Interacción del estudiantado y el bienestar subjetivo: análisis en un contexto escolar con diversidad étnica y cultural (2015)
This research article is a part of school counseling project of Las Americas School. The research forms the Master’s thesis in Education with the Technological Institute of Monterrey and UNIMINUTO.It aims to understand the ways of interaction of the students of that institution and its influence on subjective welfare, in a school context with ethnic and cultural diversity. Moreover, some available alternatives in the educational institution were identified available to ensure the student subjective welfare, which are related in the cultural diversity context. The study was conducted through qualitative phenomenological method. The semi structured interview was applied as a research instrument to a sample of twenty (20) students from different ethnic groups, as well as direct observation, as methods to strengthen the information collected. From the results, it was possible to conclude that ethnic and cultural diversity are factors that determine the students’ interactions and also influence its subjective welfare state.